DESIGN AND IMPLEMENTATION OF ACCOUNTING RECORDING SYSTEM AND FINANCIAL REPORTING AT WIRAMAS PALAPA STORE - Santi Yopie; Alfredo Cristiano (ConCEPt - Conference on Community Engagement Project, 2022)
The purpose of implementing this project is to develop an accounting and financial reporting system at one of the MSMEs in Batam, namely the Wiramas Palapa store. Wiramas Palapa store is a building shop owned by a businessman named Mr. Antoni Wibowo. Wiramas Palapa store is located at Batu Aji Centre Blok B No. 09, but the operational location has moved to the tembesi area. The accounting and financial reporting system at Wiramas Palapa stores still use a book-based system that contains data on purchases, sales, cash expenditures, and cash receipts. The technique of collecting data in this project starts from interviewing, observation, and documentation. There are five stages of practical work in the Wiramas Palapa store, namely evaluating, tidying up, studying, recording, and designing systems and reporting with six months from September - December 2021. The output of this research is a Microsoft Office Access accounting system that records the financial transactions of Wiramas Palapa stores, publishes accurate financial statements including, income statements, balance sheet statements, financial position statements, inventory statements, sales statements, purchase reports, ledgers, residual debt reports, accounts receivables, to asset lists and depreciation, so that owners can make more informed business decisions.